Digital Encyclopedia of Applied Physics 2022
DOI: 10.1002/3527600434.eap936
|View full text |Cite
|
Sign up to set email alerts
|

Nanowires and Nanotubes

Abstract: Nanowires and nanotubes are at the forefront of materials science and engineering. Owing to the unique structural one‐dimensionality and possible quantum confinement effects in two dimensions, nanowires and nanotubes exhibit many novel properties. They are considered to be critical building blocks for developing nanoscale devices. The synthesis and characterization of nanowires and nanotubes constitute an important part of the development of nanotechnology. Significant progress has been made in investigating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 222 publications
0
0
0
Order By: Relevance
“…A thickness-dependence study on ZnO films under UV illumination conducted by Su et al demonstrated the highest sensitivity at ambient temperature and found that response to the target gas (NO 2 ) increased with increasing thickness to a maximum of 1500 nm, after which the response began decreasing [21,22]. While this study highlights the significance of UV for lowering operating temperature, the thicker films possessed higher porosity which had a larger penetration depth for the UV light to create more photogenerated carriers and efficient diffusion of gas molecules [17]. This study examines, at a fundamental level, the hierarchical morphology-promoted enhancement of methane sensing from vertically aligned nanorod and networked tetrapod ZnO films, surface catalysts, and thermal and UV excitation, providing a thorough physical and chemical understanding of sensing mechanism.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…A thickness-dependence study on ZnO films under UV illumination conducted by Su et al demonstrated the highest sensitivity at ambient temperature and found that response to the target gas (NO 2 ) increased with increasing thickness to a maximum of 1500 nm, after which the response began decreasing [21,22]. While this study highlights the significance of UV for lowering operating temperature, the thicker films possessed higher porosity which had a larger penetration depth for the UV light to create more photogenerated carriers and efficient diffusion of gas molecules [17]. This study examines, at a fundamental level, the hierarchical morphology-promoted enhancement of methane sensing from vertically aligned nanorod and networked tetrapod ZnO films, surface catalysts, and thermal and UV excitation, providing a thorough physical and chemical understanding of sensing mechanism.…”
Section: Introductionmentioning
confidence: 61%
“…ZnO nanorod (ZnO-NR) thin films were prepared via the aqueous phase chemical solution growth method [16,17]. Briefly, a 25 mM zinc acetate in ethanol seed solution was prepared with 40 wt.% Au nanoparticles.…”
Section: Preparation Of Zno-nr Array Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation